Efficacy of suction blister epidermal graft without phototherapy for locally stable and resistant vitiligo - Masoud Maleki; Mahnaz Banihashemi; Vahid Sanjari (Wolters Kluwer Medknow Publications, 2012)
Introduction: Surgical methods for treatment of vitiligo include punch grafts, blister grafts, follicular grafts and cultured melanocyte grafts. The aim of this study was to determine the efficacy of suction blister grafts for treatment of vitiligo, without the use of phototherapy. Materials and Methods: This clinical trial study was conducted on 10 patients with vitiligo that was resistant to usual treatments and with limited involvement in the affected sites. We used cryotherapy and a manual suction device for blistering at the recipient and donor sites, respectively. The blister was separated and fixed with sutures and a dressing to the recipient site. Repigmentation of lesions was evaluated monthly for 6 months after treatment. Repigmentation rates higher than 90%, between 71%-90%, from 51%-70%, and less than 50% were graded as complete, good, moderate, and poor, respectively. Results: Ten patients (five females with a mean age of 23.2±3.96 years and five males with a mean age of 30.60±4.15 years) were enrolled in the study. Reponses to treatment after a 6-month follow-up were 'complete,' 'good,' and 'moderate' in 7 (70%), 1 (10%), and 2 (20%) patients, respectively. Conclusion: With this technique, patients with restricted sites of involvement, that did not respond to the usual treatments showed very good repigmentation without any additional phototherapy over a 6-month follow-up; moreover, there were no side effects such as scarring.